The Concept of Organizing the Nusantara Special Capital Regional Government (IKN) to Realize Good Governance - Farida, Anis; Rohmah, Elva Imeldatur; Huri, Daman (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
The capital is a city designed and used as the center of government of a country as well as a symbol of that country's identity. The move of the country's capital from Jakarta to East Kalimantan (the archipelago's capital) has several reasons, one of which is that Jakarta is no longer suitable for use as the country's capital. The archipelago's capital city is in the form of a particular regional government with an authority body appointed directly by the president after consultation with the DPR. Still, there is no maximum limit on the number of times a person can serve as Head and Deputy Head of the Authority Body. Apart from that, in the archipelago's capital city, there is no DPRD like in other regions, so this is a problem within the scope of Indonesian state administration. This research is included in the category of normative legal research with several approaches, namely the statutory approach and conceptual approaches, as well as using primary and secondary legal materials. The results of this research show that in the context of regional autonomy, the IKN regional government remains under the central government's jurisdiction. The central government still has a role in supervising IKN regional government activities, safeguarding national interests, and providing necessary support. Implementing the National Capital Special Regional Government (IKN) for the archipelago to realize good governance requires active community involvement in decision-making. In the absence of general elections for DPRD members in IKN Nusantara, aspects of representation and legitimacy can be questioned. In addition, an unlimited term of office for the head of the IKN Authority and his deputies could hurt the implementation of good governance. A better mechanism for regular leadership changes is needed to achieve good governance so there is a healthy rotation of power and opportunities for new and qualified leaders to lead. It can create better oversight and transparency in decision-making and minimize the risk of abuse of power.